Estimating streaming potentials associated with geothermal circulation at the Main Central Thrust: an example from Tatopani-Kodari hot spring in central Nepal - Perrier, Frederic; Chitrakar, Gyani Raja; Froidefond, Thierry; Tiwari, Dilliram; Gautam, Umesh; Kafle, Basanta; Trique, Michael (Journal of Nepal Geological Society, 2002)
Streaming potential coefficient and electrical conductivity have been measured in the laboratory as a function of KCI electrolyte conductivity for six crushed rock samples collected at the Main Central Thrust (MCT) zone, near the TatopaniKodari hot spring in Central Nepal. Surface conductivity values range from 0.11±0.07 to 1.19±0.13 mS/m and values of the inferred ζ potential vary from -16.3±0.2 mV to -41.2±1.0 mV. These experimental values are used to model the streaming potential coefficient and the rock resistivity as a function of permeability. The electric potential generated on sur face by the geothermal circulation at the MCT zone is then derived using a simple two-dimensional analytical calculation. The maximum expected anomaly depends on the values of poorly known parameters such as the permeability of the MCT but is estimated to be of the order of 20 mV, and in general tends to remain below 100 mV. Such anomalies, although they could reflect variations of crustal parameters associated with stress accumulation, are difficult to detect and do not appear as a promising possibility in the search for earthquake precursors.